Ministerial elites in Greece (2000-2019): between party, expertise and technocracy? - Karoulas, Gerasimos; Kakepaki, Manina (The Greek Review of Social Research, 2022)
The article explores the main characteristics of ministerial elites in Greece during the first two decades of the 21st century. The analysis emphasizes issues such as ministers’ sociodemographic profile, their party affiliations, their relationship with party leaders, as well as the emerging role of technocrats. Research is based on data collected under the SEGov Project, which focuses on the analysis of ministerial elites in Southern Europe. Our findings indicated a number of issues such as the limited presence of women among ministerial elites, the high educational level, the lack of interrelation between educational scientific object and portfolios’ field of activity, the diminishing role of party affiliation during the last years and finally the emerging role of technical expertise and technocrats among ministerial elites.